Divine Subjection : The Rhetoric of sacramental Devotion in Early Modern England - Kuchar, Gary, 1974- (Medieval and Renaissance literary studies., 2005)
"Combines theoretically engaged analyses with historically contextualized close readings to open new ways of understanding the relations between devotional literature and early modern English culture"--Provided by publisher.